PROPOSED STATE-OWNED ASSET MANAGEMENT ORGANIZATION STRUCTURE USING ANALYTIC HIERARCHY PROCESS - PRAMESWARA (NIM 29316126), JOHANES
In the Ministry of Energy and Mineral Resources (MEMR), Asset management is carried out by the Echelon II unit of the State-Owned Asset Management Center, referred to Bahasa Indonesia as Pusat Pengelolaan Barang Milik Negara (PPBMN), which responsible to the MEMR through the Secretariat General. PPBMN is the result of organization development in the Echelon III unit in the Finance Bureau of the MEMR. After 7 years PPBMN was formed, there is no study that has determined the effectiveness of the current organization structure of PPBMN in carrying out the activities of State-Owned Asset Management in MEMR. In addition, based on customer satisfaction surveys that were conducted by PPBMN administration section in year 2015 and 2016 there was a decrease to the speed of service, therefore, an objective study is needed on the evaluation of current organization structure of PPBMN, in order to find out whether the decline that occurred and recorded in the results of customer satisfaction survey is the impact of the current form of organizational structure, and what are the other problems faced in the current PPBMN organization. Based on the above problems, this study aims to: 1) To find out what issues are occurring within the current PPBMN organization structure. 2) To find alternatives and solutions to problems that occur within the current PPBMN organization structure. The research is using Multi Criteria Decision Making (MCDM) method which is Analytical Hierarchy Process (AHP) by using 4 criteria; Organization size, Division of work, span of communication, and formalization, and 8 sub-criteria; number of employees, authority, workload, business process, employeesÃ‚Â’ asset management knowledge, and compliance with regulations, with 4 organization structure alternatives. The multi-criteria framework is used to support the decision-making process in determining future organization structure. The weight of the criteria is determined by using pairwise comparison matrices of the AHP. The results obtained from the above analysis is the determination of the organization structure in accordance with the current condition of PPBMN and that has been determined by experts based on the existing criteria. The final result is changing the organizational structure into commodity-based organization structure.